Biological and socioeconomic determinants of prediabetes in youth: an analysis using 2007 to 2011 Canadian Health Measures Surveys. (August 2018) - Rodd, Celia; Feely, Allison; Dart, Allison; Sharma, Atul; McGavock, Jon
Abstract Objectives To describe rates of prediabetes among youth in Canada and the associated social and biological characteristics. Methods We analyzed the cross-sectional data from the first (2007–2009) and second (2009–2011) cycles of the Canadian Health Measures Survey (CHMS) for youth aged 6–19 years. Prediabetes was defined using the glycated hemoglobin (A1C) guidelines set out by the American Diabetes Association (ADA) and the Canadian Diabetes Association (CDA) of A1C ranges 5.7–6.4% (38.8–46.4 mmol/mol) and 6.0–6.4% (42.1–46.4 mmol/mol), respectively. Results An elevated A1C was observed in 22.8% of our sample (n  = 3449) based on the ADA definition and 5.2% of youth using the CDA definition. Independent predictors in a fully adjusted model for prediabetes were non-White (odds ratio (OR) 2.62: 95% Confidence intervals 2.05–3.35), obese (OR 1.53: 1.19–1.96), less physically active youth (0.97: 0.95–0.99), and parents with high school education or less (1.34: 1.02–1.74). Moreover, significant regional variations were noted with higher rates for all regions except Ontario. Conclusion Prediabetes is relatively common in Canada and associated with common biologic and socioeconomic factors. Importantly, regular physical activity was significantly associated with reduced odds of prediabetes. Targeted screening and continued emphasis on physical activity may help curb the increasing rates of prediabetes.